The Challenge of Indonesian Post Migrant Worker’s Welfare - BASROWI, BASROWI; MAUNAH, Binti (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
The aims of this study are to describe the effect of partially and simultaneously the level of income, family support, and the level of productive investment on the welfare level of Indonesian migrant workers. The research method used is quantitative research, with a correlational approach, especially at the descriptive verification level. The population of this research is as many as 2,400 people. The sampling technique chosen was purposive sampling. The number of research samples is 240 people or 10% of the total population. Data was collected using a survey method. The study was conducted in two districts in Central Java Province, Indonesia. Data analysis in this study uses inferential statistics to test hypotheses using the Structural Equation Model (SEM) formula or structural equation model with the help of software and LISREL version 8.70. Based on the results of the analysis can be concluded: there is a significant effect both partially and simultaneously between the level of income, family support, and the level of productive investment on the level of welfare of migrant workers. The most influential factor on the welfare of the Indonesian workforce is the factor of productive investment.